We Saved the Best for You Letters of Hope, Imagination and Wisdom for 21st Century Educators - Kress, Tricia M.; Lake, Robert; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
As standardization and (3z(Baccountability(3y (Bhave continued to increase in the 21st century, educators and scholars of education have become increasingly frustrated. Yet as frustrated as we are, it is essential that we not send to our our students, children, grandchildren the message that the past was better and they (3z(Bshould have been there.(3y (BInstead, we must render a clear vision of what can be. Indeed, where would we be without the vision we have been freely given to us from great scholars, philosophers, and artists, as well as our own teachers, friends, neighbors, and family? We are indebted to carry forward the legacy of these torchbearers to present and future educators. This book is a collection of letters to 21st century educators of all age levels and content areas. It has been compiled with the goal of fulfilling our responsibility to share with the next generation of educators our vision of the future, just as our predecessors and role models shared theirs with us. Informed by the past but oriented toward the future, this collection aims to inspire in present and future educators hope, wisdom and imagination for addressing the educational challenges shaped by bureaucratic, economic and cultural forces. Authors such as Nel Noddings, Sonia Nieto, Sandy Grande, Riane Eisler, Mike Rose, William Schubert, William Reynolds, and many more speak directly to their readers, building a relationship with a scholarly backbone, and encouraging: (3z(Bwe saved the best for you(3y (Bbecause (3z(Bthe best(3y (Bis the world you will create.s
Keywords: Education; Education; Education (general).